KARAKTERISTIK STUDI ISLAM: PENDEKATAN SECARA HISTORIS - Tiara Puspa Tsurayya; Jawiyah; Eko Nursalim (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This article explores the characteristics of Islamic studies through a historical approach, with a particular emphasis on changes that have occurred in Islamic thought, society, and culture, especially in Indonesia. In this study, a literature review method was used. The data used included books, journals, articles, and relevant digital documents. The results of the study show that Islam is not only a religious teaching but also a historical phenomenon that shapes civilisation, education, and culture. The character of Islam in Indonesia has developed into a normative, cultural, pluralistic, and neo-modernist one. In addition, Islamic educational institutions, such as madrasas and Islamic boarding schools, play an important role in developing educational models that are incorporated into the national system. The results confirm that by using a historical approach, Islamic research can explain the close relationship between religion, science, and culture in building an advanced Islamic civilisation.